PENGARUH RATING, ULASAN DAN GRATIS ONGKIR TERHADAP MINAT BELI KONSUMEN PADA APLIKASI SHOPEE (Studi Kasus Pada Mahasiswa Universitas Muhammadiyah Bengkulu) - Kusnadi, Yogi; Islamuddin, Islamuddin (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
This study aims to determine the effect of ratings, reviews, and free shipping on consumer buying interest in the Shopee application (case study on students of the University of Muhammadiyah Bengkulu). This type of research uses quantitative research, the population in this study is students of the University of Muhammadiyah Bengkulu with a sample of 140 respondents, using statistics agree-disagree with an interval scale of 1 to 5 measured using the Likert scale. Data analysis techniques use Multiple Linear Regression Analysis, Coefficient of determination (R2), and Hypothesis Test. Rating (X1), Reviews (X2), and Free Shipping (X3) influence Buying Interest (Y), this can be seen in the F test which states the value of F_count>F_table, namely (9.866 > 2.79) and (sig = 0.001 < 0.05), thus it can be concluded that accepted means simultaneously the variables   Rating (X_1), Review  (X_2) and Free Shipping   (X_3)    has a significant influence on Buying Interest (Y). The results of the research conducted that the research conducted in this study show that Rating, Reviews, and Free Shipping affect Buying Interest (Y) in University of Muhammadiyah Bengkulu Students who use the Shopee application. This is intended from the Coefficient of Correlation and Determination that this study has an influence value of R = 0.885 and determination of R  2 = 0.783  where this study there are variables that are not studied are 0.783 or 7.83%. Keywords: Rating, Reviews, Free Shipping, and Buying Interest